2023
DOI: 10.3390/healthcare11091224
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychological Hardiness and Military Performance by Reservists: A Moderation Effect of Perceived Stress and Resilience

Abstract: The purpose of this study is to evaluate the effect of hardiness on the perceived military performance of reservists, i.e., young people who have full-time jobs in a civilian sector and perform military training as a part of their civic duty. We proposed the conceptual model with conditional indirect effects of the hardiness on personal military performance, where mediated moderation effects are observed from personality traits and variables important for military service: team cohesion, perceived stress, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Subsequently, confirmatory factor analysis was rigorously conducted to assess the validity of the constructed model, which includes five distinct constructs. The results clearly demonstrated satisfactory convergent validity, meeting established criteria ( Byrne, 2013 ; Bekesiene et al, 2023 ). Importantly, all factor loadings were statistically significant at the value of p <0.001 level, affirming the robustness of the model and providing a solid foundation for subsequent stages of analysis and interpretation.…”
Section: Resultssupporting
confidence: 53%
“…Subsequently, confirmatory factor analysis was rigorously conducted to assess the validity of the constructed model, which includes five distinct constructs. The results clearly demonstrated satisfactory convergent validity, meeting established criteria ( Byrne, 2013 ; Bekesiene et al, 2023 ). Importantly, all factor loadings were statistically significant at the value of p <0.001 level, affirming the robustness of the model and providing a solid foundation for subsequent stages of analysis and interpretation.…”
Section: Resultssupporting
confidence: 53%
“…Self-efficacy beliefs are developed from a variety of sources, including personal experiences, social persuasion, vicarious learning (observing others), and physiological and emotional states. These beliefs influence individuals’ choices, efforts, and resilience in the face of difficulties ( Kanapeckaitė et al, 2022 ; Bekesiene et al, 2023 ). Recent research on occupational self-efficacy showed that self-efficacy increases persons’ belief and confidence in performing the tasks, challenges, and stresses associated with their profession ( Li et al, 2022 ; Mei et al, 2022 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Therefore, self-efficacy, which refers to an individual’s belief in their ability to complete tasks, overcome obstacles, and succeed in specific situations, plays a critical role in the ability of soldiers to deal effectively with unexpected circumstances ( Boe et al, 2018 ). According to social cognitive theories ( Bandura, 1997 ) academic self-concept and self-efficacy can play a significant role in determining one’s motivation, perseverance, and resilience ( Djourova et al, 2020 ; Bekesiene et al, 2022 ; Kanapeckaitė et al, 2022 ; Bekesiene et al, 2023 ). As military professionals often encounter high-stress situations that require quick decision making and effective problem-solving ( Myrseth et al, 2018 ; Smaliukiene et al, 2022 ), the strong self-efficacy helps them manage stress by improving their belief in their ability to cope with and overcome challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Cadets resilience was found to affect their self-efficacy positively. Military resilience involves maintaining high levels of operational readiness even in the face of changing and unpredictable circumstances ( Beckner et al, 2022 ; Bekesiene et al, 2022 , 2023 ; Flood and Keegan, 2022 ). This readiness enables military forces to respond promptly and effectively to various threats, whether they are natural disasters or security challenges.…”
Section: Discussionmentioning
confidence: 99%